Ocular Involvement in Children with Inflammatory Bowel Disease. - Naviglio, Samuele; Parentin, Fulvio; Nider, Silvia; Rassu, Nicolò; Martelossi, Stefano; Ventura, Alessandro (Inflamm Bowel Dis, 2017)
BACKGROUND: Data on ocular manifestations of inflammatory bowel disease (IBD) in children are limited. Some authors have reported a high prevalence of asymptomatic uveitis, yet the significance of these observations is unknown and there are no recommendations on which ophthalmologic follow-up should be offered. METHODS: Children with IBD seen at a single referral center for pediatric gastroenterology were offered ophthalmologic evaluation as part of routine care for their disease. Ophthalmologic evaluation included review of ocular history as well as slit-lamp and fundoscopic examination. Medical records were also reviewed for previous ophthalmologic diagnoses or complaints. RESULTS: Data from 94 children were included (52 boys; median age 13.4 yr). Forty-six patients had a diagnosis of Crohn's disease, 46 ulcerative colitis, and 2 IBD unclassified. Intestinal disease was in clinical remission in 70% of the patients; fecal calprotectin was elevated in 64%. One patient with Crohn's disease had a previous diagnosis of clinically manifest uveitis (overall uveitis prevalence: 1.06%; incidence rate: 0.3 per 100 patient-years). This patient was also the only one who was found to have asymptomatic uveitis at slit-lamp examination. A second patient had posterior subcapsular cataract associated with corticosteroid treatment. No signs of intraocular complications from previous unrecognized uveitis were observed in any patient. CONCLUSIONS: Children with IBD may have asymptomatic uveitis, yet its prevalence seems lower than previously reported, and it was not found in children without a previous diagnosis of clinically manifest uveitis. No ocular complications from prior unrecognized uveitis were observed.
Keywords: Adolescent; Child; Child, Preschool; Feces; Female; Humans; Inflammatory Bowel Diseases; Italy; Leukocyte L1 Antigen Complex; Male; Remission Induction; Uveitis

Early onset bilateral anterior uveitis preceding a late manifestation of juvenile idiopathic arthritis: a case report. - Parentin, Fulvio; Matarazzo, Lorenza; Lepore, Loredana; Pensiero, Stefano; Ventura, Alessandro (Ocul Immunol Inflamm, 2015)
Keywords: Adolescent; Arthritis, Juvenile; Female; Humans; Time Factors; Tomography, Optical Coherence; Uveitis, Anterior

Safety and efficacy of infliximab and adalimumab for refractory uveitis in juvenile idiopathic arthritis: 1-year followup data from the Italian Registry. - Zannin, Maria E; Birolo, Carolina; Gerloni, Valeria M; Miserocchi, Elisabetta; Pontikaki, Irene; Paroli, Maria P; Bracaglia, Claudia; Shardlow, Alison; Parentin, Fulvio; Cimaz, Rolando; Simonini, Gabriele; Falcini, Fernanda; et al. (J Rheumatol, 2013)
OBJECTIVE: To evaluate safety and efficacy of adalimumab (ADA) and infliximab (IFX) for the treatment of juvenile idiopathic arthritis-related anterior uveitis (JIA-AU). METHODS: Starting January 2007, patients with JIA-AU treated with IFX and ADA were managed by a standard protocol and data were entered into the National Italian Registry (NIR). At baseline, all patients were refractory to standard immunosuppressive treatment and/or were corticosteroid-dependent. Data recorded every 3 months included uveitis course, number/type of ocular complications, drug-related adverse events (AE), treatment change or withdrawal, and laboratory measures. Data of patients treated for at least 1 year were retrieved from the NIR and analyzed using descriptive statistics. Treatment efficacy was based on change in uveitis course and in number of ocular complications. RESULTS: Up to December 2009, data for 108 patients with JIA-AU treated with anti-tumor necrosis factor-α agents were recorded in the NIR and data from 91, with at least 12 months' followup, were included in the study. Forty-eight patients were treated with IFX, 43 with ADA. Forty-seven patients (55.3%) achieved remission of AU, 28 (32.9%) had recurrent AU, and 10 (11.8%) maintained a chronic course. A higher remission rate was observed with ADA (67.4% vs 42.8% with IFX; p = 0.025). Ocular complications decreased from 0.47 to 0.32 per subject. Five patients experienced resolution of structural complications. No patient reported serious AE; 8 (8.8%) experienced 11 minor AE (9 with IFX, 2 with ADA). CONCLUSION: IFX and ADA appear to be effective and safe for treatment of refractory JIA-related uveitis, with a better performance of ADA in the medium-term period.
Keywords: Adolescent; Antibodies, Monoclonal; Antibodies, Monoclonal, Humanized; Antirheumatic Agents; Arthritis, Juvenile; Child; Child, Preschool; Female; Follow-Up Studies; Humans; Infant; Italy; Male; Registries; Treatment Outcome; Tumor Necrosis Factor-alpha; Uveitis

Congenital aplasia of the optic chiasm and esophageal atresia: a case report. - Pensiero, Stefano; Cecchini, Paolo; Michieletto, Paola; Pelizzo, Gloria; Madonia, Maurizio; Parentin, Fulvio (J Med Case Rep, 2011)
INTRODUCTION: The complete absence of the chiasm (chiasmal aplasia) is a rare clinical condition. Hypoplasia of the optic nerve and congenital nystagmus are almost invariably associated characteristics. Microphthalmos or anophthalmos are common features in chiasmal aplasia, while central nervous system abnormalities are less frequent. Esophageal atresia can be isolated or syndromic. In syndromic cases, it is frequently associated with cardiac, limb, renal or vertebral malformations and anal atresia. More rarely, esophageal atresia can be part of anophthalmia-esophageal-genital syndrome, which comprises anophthalmia or microphthalmia, genital abnormalities, vertebral defects and cerebral malformations. Here, a previously unreported case of chiasmal aplasia presenting without microphthalmos and associated with esophageal atresia is described. CASE PRESENTATION: Aplasia of the optic chiasm was identified in a Caucasian Italian 8-month-old boy with esophageal atresia. An ultrasound examination carried out at 21 weeks' gestation revealed polyhydramnios. Intrauterine growth retardation, esophageal atresia and a small atrial-septal defect were subsequently detected at 28 weeks' gestation. Repair of the esophageal atresia was carried out shortly after birth. A jejunostomy was carried out at four months to facilitate enteral feeding. The child was subsequently noted to be visually inattentive and to be neurodevelopmentally delayed. Magnetic resonance imaging revealed chiasmal aplasia. No other midline brain defects were found. His karyotype was normal. CONCLUSION: If achiasmia is a spectrum, our patient seems to depict the most severe form, since he appears to have an extremely severe visual impairment. This is in contrast to most of the cases described in the literature, where patients maintain good--or at least useful-- visual function. To the best of our knowledge, the association of optic nerve hypoplasia, complete chiasmal aplasia, esophageal atresia and atrial-septal defect, choanal atresia, hypertelorism and psychomotor retardation has never been described before.

Corneal curvature and thickness development in premature infants. - De Silva, Silvana; Parentin, Fulvio; Michieletto, Paola; Pensiero, Stefano (J Pediatr Ophthalmol Strabismus, 2011)
PURPOSE: Analysis of postnatal changes in central corneal thickness (CCT) and corneal curvature (CC) in premature infants, their relation, and their possible influence on eye growth and intraocular pressure (IOP) evaluation. METHODS: CCT and CC were assessed in both eyes of 56 premature infants, born at 24 to 32 weeks of gestational age (GA), and then two or three times at post-conceptional ages (PCAs) of 28 to 42 weeks. RESULTS: CC changed from 65.83 diopters at 28 weeks of PCA to 49.38 diopters at 42 weeks of PCA. CCT decreased from 794 to 559 μm at the same ages. The reductions of these two corneal parameters seem to be related to each other and begin immediately after birth. CONCLUSION: In light of the few data available in the literature, these data provide more certainty about the CCT values of premature infants. The importance of CCT and CC fast variations after premature birth concerns both the knowledge of anterior segment development and the correct evaluation of IOP in immature eyes; the influence of these two parameters on the methods of IOP evaluation could be more remarkable at the lowest PCAs.
Keywords: Child Development; Cornea; Corneal Pachymetry; Eye; Female; Gestational Age; Humans; Infant, Newborn; Infant, Premature; Intraocular Pressure; Male; Premature Birth

Horizontal gaze palsy and progressive scoliosis without ROBO3 mutations. - Abu-Amero, Khaled K; Faletra, Flavio; Gasparini, Paolo; Parentin, Fulvio; Pensiero, Stefano; Alorainy, Ibrahim A; Hellani, Ali M; Catalano, Dario; Bosley, Thomas M (Ophthalmic Genet, 2011)
BACKGROUND: To describe clinical and genetic observations in a patient with horizontal gaze palsy and progressive scoliosis (HGPPS) without identified mutations in the ROBO3 gene. MATERIALS AND METHODS: Neurologic and orthopedic evaluation of the proband; sequencing all exons, exon-intron boundaries, and promoter region of ROBO3 in the proband and his mother. Array CGH was also carried out in the proband and his mother to evaluate possible chromosomal deletion(s) and/or duplication(s). RESULTS: The proband had complete horizontal gaze restriction with full vertical gaze and small amplitude horizontal pendular nystagmus. He also had severe scoliosis and brainstem hypoplasia pathognomonic of HGPPS. However, complete sequencing of ROBO3 twice in both forward and reverse directions did not reveal any mutations. Array CGH investigation revealed no chromosomal abnormalities. CONCLUSIONS: This patient had clinical and neuroimaging characteristics considered pathognomonic of HGPPS and yet did not have ROBO3 mutations. A clinical misdiagnosis is unlikely in the absence of facial weakness (typical of Moebius syndrome), deafness (typical of the HOXA1 spectrum), or mental retardation (typical of other central decussation abnormalities). It is perhaps more likely that a phenotype identical to HGPPS can be caused by abnormalities in ROBO3 splice variant expression, by mutations of a gene other than ROBO3, or by some environmental or epigenetic factor(s) inhibiting the action of ROBO3 or its protein product in the developing brainstem.
Keywords: Child; Humans; Kyphosis; Magnetic Resonance Imaging; Male; Mutation; Ocular Motility Disorders; Oculomotor Nerve Diseases; Pedigree; Receptors, Immunologic; Scoliosis

Paediatric Behçet's disease presenting with recurrent papillitis and episcleritis: a case report. - Parentin, Fulvio; Lepore, Loredana; Rabach, Ingrid; Pensiero, Stefano (J Med Case Rep, 2011)
INTRODUCTION: Behçet's disease is a chronic multisystem vasculitis characterized by mucocutaneous, articular, neurological, gastrointestinal and ophthalmological lesions. Ocular involvement is mainly represented by recurrent uveitis, especially posterior uveitis; however, iridocyclitis, retinal and choroidal vasculitis, optic neuritis and retinal vascular occlusion can also occur. CASE PRESENTATION: A 12-year-old Caucasian boy with a history of recurrent buccal aphthosis and nonspecific gastrointestinal symptoms was admitted to our hospital with blurred vision associated with acute episcleritis and papillitis. The patient's pathergy test was positive, suggesting a diagnosis of Behçet's disease. Corticosteroid and cyclosporine therapy was started, but further episodes were noted in both eyes. The patient was then switched to intravenous infliximab, with complete resolution of the inflammation after the second infusion. CONCLUSION: Episcleritis and papillitis should be added to the list of uncommon manifestations of pediatric Behçet's disease. Infliximab is an effective, new therapeutic approach for Behçet's disease that is refractory to the conventional corticosteroid and immunosuppressive therapy.

A singular case of congenital self-healing histiocytosis with skin, liver and atypical eye involvement. - Parentin, Fulvio; Ventura, Giovanna; Pastore, Serena; Kiren, Valentina; Bibalo, Chiara; Pensiero, Stefano; Lepore, Loredana (Ocul Immunol Inflamm, 2011)
PURPOSE: To describe a rare case of congenital self-healing Langerhans cell histiocytosis (CSHLCH) presenting with atypical eye involvement. DESIGN: Case report. METHODS: A female newborn presented with purpuric lesions over the trunk, limbs, and face. Liver ultrasonography revealed hypoechogenic lesions with blurred borders. Biomicroscopy showed right posterior synechiae with fibrinoid deposits on the lens. At 7 months she presented with right acute glaucoma. RESULTS: Biomicroscopy showed the presence of inflammatory pseudo-membrane covering the anterior surface of the lens, iris, and iridocorneal angle. Ab externo trabeculotomy was performed; access to the anterior chamber with capsulorrhexis forceps permitted a peeling of the pseudo-membrane with normalization of the intraocular pressure. Histologic examination of the membrane revealed an inflammatory tissue with CD1a and S-100 positive histiocytic cells. CONCLUSIONS: This is the first case of CSHLCH describing acute glaucoma secondary to a pseudo-inflammatory membrane with typical histiocytic cells, occluding the iridocorneal angle.
Keywords: Antigens, CD1; Convalescence; Female; Glaucoma; Histiocytosis, Langerhans-Cell; Humans; Infant; Intraocular Pressure; Iridocorneal Endothelial Syndrome; Liver Diseases; S100 Proteins; Skin Diseases; Trabeculectomy

Eye movement impairment recovery in a Gaucher patient treated with miglustat. - Accardo, Agostino; Pensiero, Stefano; Ciana, Giovanni; Parentin, Fulvio; Bembi, Bruno (Neurol Res Int, 2010)
In Gaucher Disease (GD) the enzyme (imiglucerase) replacement therapy (ERT) is not able to stop the progression of the neurological involvement, while the substrate reduction therapy (SRT), performed by N-Butyldeoxynojirimycin (miglustat), is an alternative that should be evaluated. Two sisters, presenting the same genotype (R353G/R353G), were diagnosed as suffering from GD; one of them later developed neurological alterations identified by quantitative saccadic eye movements analysis. The aim of the study was to quantitatively measure the miglustat effects in this GD neurological patient. Eye movement analysis during subsequent controls was performed by estimating the characteristic parameters of saccadic main sequence. The study demonstrates that the SRT alone can be effective in GD3. Moreover, it confirms that quantitative eye movement analysis is able to precociously identify also slight neurological alterations, permitting more accurate GD classification.